Separation, preconcentration and determination of rare earth elements by inductively coupled plasma emission spectroscopy - Cracknell, R H (Department of Physics, 2017)
Rare earth elements, (REE), at ug g⁻¹ levels are used for studies of petrogenisis of different geological materials. For these studies, the REE must be determined precisely. An analytical program was established using an IL 200 Inductively Coupled Plasma, (ICP), spectrometer for the determination of the REE in various matrices, taking into consideration both matrix and spectral interferences, which were found to be severe in some cases. Dissolution of the sample, (0.4-1.0 g), was carried out using two methods; a microwave heated dissolution using a modified commercial microwave oven and a conventional oven heated closed pressure digestion vessel method. The results of these two methods were compared to determine the viability of using the more rapid microwave heated method. Separation of the REE from matrix elements was investigated using three cation exchange resins; Amber lite IR 120 (H), Zeocarb 225 and Dowex 50-WXS. A gradient acid elution method was established using a 15 cm by 20 mm Zeocarb 225 column. The sample was eluted with 140 ml of a 1.5 M H⁺ solution containing 0.75 M Cl⁻ and 0.75 M NO₃⁻, this fraction containing all the matrix elements. The REE were then eluted from the resin with 100 ml of 3 M HNO₃. The REE containing fraction was then reduced to 5 ml, diluted to 10 ml, and analysed for REE content. Liquid-liquid extraction methods for the separation of REE from matrix elements were investigated. It was found that the REE could be extracted synergistically from various buffered aqueous acidic media into chloroform, (CHCl₃), by hexafluoroacetylacetone, (HHFA), and quinoline. Acetylacetone, ( AcAc), was found to react with hexamethylenetetramine, (hexamine), when hexamine was used to buffer the aqueous phase during extraction procedures. The product of this reaction, 3.5-diacetyl-1.4-dihydro-2.6-dimethyl pyridine, was identified using X-ray crystallography.